Role of cTnT Versus Echocardiography in Diagnosing the Early Myocardial Injury in Children on Doxorubicin for Cancer Chemotherapy: A Cross-sectional Study in a Tertiary Referral Centre in Kenya - Kariuki, Nyambura; Kimani, Esther; Jowi, Christine; Wamalwa, Dalton; Suen, Jacky Y.; Fraser, John F.; Obonyo, Nchafatso G. (Medical Science: Trends and Innovations Vol. 6, 2025)
Introduction: The mainstay of management of most paediatric malignancies is chemotherapy which has significantly increased the survival of most children with malignancies from 20–30% in the 1960s when chemotherapy was introduced, to 83% in 2014. However, the use of some of these chemotherapeutic agents such as anthracyclines is limited by their toxicity profiles, especially cardiac toxicity. Use of doxorubicin, an anthracycline chemotherapeutic agent has been associated with late-occurring cardiac toxicities. Detection of early occurring cardiac effects of cancer chemotherapy is essential to prevent the occurrence of adverse events including toxicity, myocardial dysfunction, and death. Objective: The objective of the study is to investigate the prevalence of elevated cardiac troponin T (cTnT) and associated factors of myocardial injury in children on doxorubicin cancer chemotherapy. Methods: A cross-sectional study design was adopted. It is a hospital-based study conducted on children aged 1 month to 12.4 years who had a diagnosis of cancer and were admitted at Kenyatta National Hospital (KNH). Interventions and Outcomes: The patients underwent Echocardiography (ECHO) before their scheduled chemotherapy infusion. Twenty-four (24) hours after the chemotherapy infusion the patients had an evaluation of the serum cardiac troponin T (cTnT) and a repeat ECHO. Myocardial injury was defined as a cTnT level > 0.014 ng/ml or a Fractional Shortening (FS) of < 29% on ECHO. Data Analysis: Data collected were entered into a patient data sheet and then transcribed to a computer database, SPSS version 23.0. Descriptive, univariate, and multivariate analyses were done to determine the factors associated with elevated cTnT. Results: One hundred (100) children were included in the final analysis. Thirty-two percent (32%) of the study population had an elevated cTnT. A cumulative doxorubicin dose of > 175 mg/m2 was significantly associated with an elevated cTnT (OR, 10.76; 95% CI, 1.18–97.92; p = 0.035). Diagnosis of nephroblastoma was also associated with an elevated cTnT (OR, 3.0; 95% CI, 1.23–7.26) but not statistically significant (p = 0.105). Nine percent (9%) of the participants had echocardiographic evidence of myocardial injury. In evaluating anthracycline-induced cardiac injury for paediatric cancer patients, troponins are reliable biomarkers since repeated anthracycline chemotherapy exposure leads to detectable troponin levels in the peripheral circulation. This is consistent with findings from our study whereby 77% of patients were exposed to anthracyclines with 32% having elevated levels of cTnT in a median treatment duration of 3 months. Conclusion: When compared to echocardiography, elevated levels of cTnT showed a higher association with early occurring chemotherapy-induced myocardial injury among children on cancer treatment at a tertiary teaching and referral hospital in Kenya. The study recommends that future research in this field should explore the utility of cTnT as a screening test for the detection of early-occurring myocardial injury among cancer patients commencing chemotherapy and follow-up patients for a longer duration of time.